2009
DOI: 10.1007/s00125-009-1557-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association analysis of LARS2 with type 2 diabetes

Abstract: Aims/hypothesis LARS2 has been previously identified as a potential type 2 diabetes susceptibility gene through the low-frequency H324Q (rs71645922) variant (minor allele frequency [MAF] 3.0%). However, this association did not achieve genome-wide levels of significance. The aim of this study was to establish the true contribution of this variant and common variants in LARS2 (MAF>5%) to type 2 diabetes risk.Methods We combined genome-wide association data (n= 10,128) from the DIAGRAM consortium with independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Interestingly, one CpG site mediating (cg15733049, Chromosome 1:2334974) FAM214A is found in low-DNase activity sites in placenta samples taken at various timepoints; additionally, cg15733049 is local to EPS15 , the RP predicted to mediate genetic regulation of FAM214A . Furthermore, expression of LARS2 , a TWAS gene for adult BMI, is mediated by cg04097236 (found within ELOVL2 ), a CpG site found in low DNase or high H3K27 activity regions; LARS2 houses multiple GWAS risk SNPs for type 2 diabetes 54 and has shown adult BMI TWAS associations in other tissues 17 , 28 . Results from these external datasets add more evidence that these mediators play a role in gene regulation of these TWAS-identified genes and should be investigated experimentally in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, one CpG site mediating (cg15733049, Chromosome 1:2334974) FAM214A is found in low-DNase activity sites in placenta samples taken at various timepoints; additionally, cg15733049 is local to EPS15 , the RP predicted to mediate genetic regulation of FAM214A . Furthermore, expression of LARS2 , a TWAS gene for adult BMI, is mediated by cg04097236 (found within ELOVL2 ), a CpG site found in low DNase or high H3K27 activity regions; LARS2 houses multiple GWAS risk SNPs for type 2 diabetes 54 and has shown adult BMI TWAS associations in other tissues 17 , 28 . Results from these external datasets add more evidence that these mediators play a role in gene regulation of these TWAS-identified genes and should be investigated experimentally in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…Using purified islets from multiple GIT2KO or WT ( n ≥ 3) mice, a differentially regulated transcriptomic profile was generated (Table S14 in Supplementary Material). At the basic transcriptomic level multiple transcripts closely linked to diabetic pathology and islet dysfunction were differentially regulated in GIT2KO compared to WT islets, e.g., Slc2a2 [glucose transporter 2 ( 78 )], Reg3a/b [regenerating islet-derived protein 3 alpha/beta ( 79 )], Ffa2 [free fatty acid receptor 2 ( 80 )], Trib3 [tribbles homolog 3 ( 81 )], PP [pancreatic polypeptide ( 82 )], Sesn1 [sestrin 1 ( 83 )], Glo1 [glyoxylase 1 ( 84 )], and Lars2 [leucyl-tRNA synthetase 2, mitochondrial ( 85 )]. Using “pancreas-specific” tissue database signaling investigation with IPA, we applied Disease/Bio-Function annotation to the GIT2KO islet transcriptome data (Table S15 in Supplementary Material).…”
Section: Resultsmentioning
confidence: 99%
“…A study in 7836 individuals from the Netherlands and Denmark identified a pathogenic missense H324Q variant in the LARS2 gene, encoding mitochondrial leucyl-tRNA synthetase which catalyses the aminoacylation of mt-tRNA Leu (UUR) , as associated with T2D [75]. This initial association could, however, not be replicated in a much larger follow-up study [137]. The importance of preserved tRNA aminoacylation for proper β-cell function is illustrated by the association between impaired mt-tRNA Leu (UUG) charging and MIDD [138][139][140].…”
Section: Pathogenic Variants In Aarssmentioning
confidence: 99%